URGNT AND ESSENTIAL: Music in Times of Crisis - Marczyk, Mark (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Mark Marczyk describes the creation of the URGNT livestream series to broadcast from empty Toronto music venues in the early days of the pandemic.